The Social, Economic, and Ecological Drivers of Planning and Management of Urban River Parks - Zingraff-Hamed, Aude; Serra-Llobet, Anna; Kondolf, G. Mathias (Frontiers in Sustainable Cities, 2022)
Urban rivers deliver a broad range of contributions of nature to human development. The exploitation of the riverine ecosystem services evolves with uncertainty. In addition to the current decreasing of ecosystem health and changing climate, the impact of societal development on the river system directly reduces the potential delivery of future ecosystem services. What are the drivers of the design of urban river parks and what upcoming challenges will need to be addressed? This paper presents the results of an ex-post-analysis and comparative analysis of planning orientations of two urban river parks, the Isar River in Munich (Germany) and the American River in Sacramento (U.S.). The contribution describes the evolution of the urban rivers based on planning strategy, identifies drivers of changes and discusses the upcoming challenges for urban river parks that need to be addressed in the short and long term. The contribution show that urban river park designs occur in a large context of human demographic, technological, and economic changes. The contribution does not intend to solve the very complex and urgent challenges the case study sites face but rather to highlight research needs to support adaptation strategies.